Audit Perspective on The Principles of Village Financial Management - Kartim, K.; Mariani, Siti; Pertiwi, Dian; Aldrin Akbar, Mohammad; Ibrahim, Muhdi B. Hi. (Manunggal Halim Jaya, 2022)
Study done with aim for know: (1) Application principal management finance village in stages cycle management finance village; (2) How to upgrade transparency and accountability management finance village (3) Top audit perspective principal management finance village in the District Awangpone Bone County. Implementation study in the process using primary data, namely the data obtained live from Government Bone District on Service Empowerment Public and Village; Government Subdistrict Awangpone, Government The village in question, Chief and member Body deliberative Village, community the village concerned, Office of the Community Development Empowerment Program Village (P3MD) Bone Regency, and Public the village concerned. While the secondary data, namely the data/information obtained through reference or literatures as well as related documents with tree discussion research. Obtained data then analyzed with technique analysis frame. Results research that has done by writer show that: (1) Application principle management finance village in stages cycle management finance village still need level; (2) How to upgrade transparency and accountability management finance village is Upgrade participation active Public village in stages cycle management finance village; and (3) Necessary will together from various related parties (community, BPD, Head village, and Local Government) for involve Public in a manner active in stages cycle management finance village.